The Global Crisis and Transformative Social Change
XVI, 289 p.
Keywords: Global crises not only deeply impact the economy and people's livelihoods, they also unsettle basic ideas and assumptions about the meaning and drivers of development. This collection of theoretical and empirical studies explores the substance and politics of policy change following the 2007/8 crisis from the perspective of developing countries.